Only consciousness truly exists? Two problems for IIT 4.0’s ontology - Cea, Ignacio; Negro, Niccolo; Signorelli, Camilo Miguel (Frontiers in Psychology, 2024)
In this article we present two ontological problems for the Integrated Information Theory of Consciousness 4.0: what we call the i) the intrinsicality 2.0 problem, and ii) the engineering problem. These problems entail that truly existing, conscious entities can depend on, and be engineered from, entities that do not objectively exist, which is problematic: if something does not exist in objective reality (i.e., in itself, independently of another entity's consciousness), then it seems that it cannot be part of the material basis and determinants of other entities that do exist on their own. We argue that the core origin of these problems lies in IIT's equation between true existence and phenomenal existence (consciousness), and the corresponding ontological exclusion of non-conscious physical entities (i.e., extrinsic entities) from objective reality. In short, these two problems seem to show that IIT should reconsider the ontological status of these extrinsic entities, because they need to exist objectively to account for the ontological implications of the scenarios we present here, which are permitted by the operational framework of the theory.Currently, Integrated Information Theory (IIT) is recognized as one of the leading scientific theories of consciousness (Seth and Bayne 2022;Consortium et al. 2023;Signorelli, Szczotka, and Prentner 2021). In contrast to other prominent theories, like the Global Neuronal Workspace Theory (Dehaene